The Role of Elementary School Teachers' Digital Literacy in Improving 21st Century Skills in Students - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
The 21st century requires students to master critical thinking, creativity, communication, and collaboration skills, which cannot be separated from teachers' digital literacy as learning facilitators. This study aims to analyze the role of elementary school teachers' digital literacy in improving students' 21st-century skills. The method used is quantitative with a survey approach to elementary school teachers who have experience in using digital technology in the classroom. Data were collected through a structured questionnaire and analyzed using SmartPLS-assisted Structural Equation Modeling (SEM). The results show that teachers' digital literacy has a significant and positive effect on all dimensions of 21st-century skills, with the greatest effect on creativity (β = 0.62, p < 0.001), followed by communication (β = 0.55, p < 0.001), collaboration (β = 0.48, p = 0.002), and critical thinking (β = 0.41, p = 0.004). These findings confirm that teachers' digital literacy is not limited to technical competence, but also serves as a pedagogical resource for designing innovative learning. However, the descriptive results show that collaboration and critical thinking are still at a moderate level, requiring more targeted instructional strategies. This study concludes that improving teachers' digital literacy must be accompanied by strengthening technology-based pedagogical strategies so that students' 21st-century skills can develop comprehensively.